Integrating Blockchain and Smart Contracts for Carbon Credit Management in Thailand: A Preliminary Multidisciplinary Analysis - Phanthika Trakunsathitman; Chiratt Chaisamran; Thattapon Surasak (My University, 2025)
Blockchain and smart contracts have emerged as transformative technologies for enhancing transparency, security, and automation in carbon credit management. This study explores the integration of these technologies within the context of Thailand’s carbon markets, focusing on system design, user interface development, and blockchain architecture. A UX testing phase was conducted to evaluate usability, security perception, and transaction efficiency. The results demonstrate strong stakeholder trust in blockchain’s security benefits while identifying areas for improvement in user guidance and error feedback. While blockchain-based carbon credit platforms exist globally, this study examines their feasibility in Thailand and highlights potential challenges, including policy considerations and stakeholder engagement. The findings suggest that blockchain and smart contracts can enhance market transparency and compliance mechanisms, paving the way for further research into their broader adoption in sustainability initiatives.
Keywords: FinTech, Crowdfunding, Digital Finance; Blockchain Technology Applications and Security